PENGARUH KEPUASAN KERJA DAN BUDAYA ORGANISASI TERHADAP KOMITMEN ORGANISASIONAL DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR PERAWAT - I Gede Aryana Mahayasa; Desak Ketut Sintaasih; Made Surya Putra (Faculty of Economics and Business Udayana University, 2018)
The purpose of this study was to analyze the influence of organizational culture and employee satisfaction to organizational commitment and organizational citizenship behavior (OCB) of nurses. The research population were nurses from private general hospital type C in the city of Denpasar with number of respondents were 85 nurses. Sampling technique conducted with a random proportional sampling technique. The research instrument used questionnaires and analyzed with Structural Equation Model-Partial Least Square (PLS-SEM). The results showed that the organizational culture has a positive and significant influence on organizational commitment and OCB, employee satisfaction has a positive and significant influence on organizational commitment and OCB.